miR-6869-5p Inhibits Glioma Cell Proliferation and Invasion via Targeting PGK1 - Fakai Wang; Huanjun Zhang; Bing Liu; Wei Liu; Zengchao Zhang (Hindawi Limited, 2020)
Accumulating studies have suggested the dysregulated microRNAs (miRNAs) play important roles in brain tumors, including glioma. miR-6869-5p has been documented to be aberrantly expressed in diverse cancers. However, the precise role of miR-6869-5p in glioma remains poorly understood. This study is aimed at evaluating its modifying effects on glioma. Significantly decreased expression of miR-6869-5p was found in glioma tissues and cells. Negative association was documented between miR-6869-5p and PGK1 in glioma cells, and PGK1 was demonstrated to be a targeted gene of this miRNA by luciferase reporter assay. miR-6869-5p regulated glioma cell proliferation and invasion via targeting PGK1. In addition, the survival analysis had suggested that low miR-6869-5p expression predicted poor prognosis of glioma patients. This study has suggested that miR-6869-5p is a useful tumor suppressor and prognostic marker in glioma.